The Behavior and Market Efficiency of Aglaonema Ornamental Plants in Baubau - Waode Alzarliani; Wa Ode Dian Purnamasari; Nabila Gafur (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Buton, 2021)
This research aims to look at the behavior and market efficiency of Aglaonema ornamental plants in Baubau, Indonesia. Furthermore, each agency's marketing channels, margins, expenses, and benefits are analyzed for technical and economic efficiency. In addition, 40 farmers were sampled using the census technique, and an institutional approach was taken utilizing the snowball method. The findings demonstrate that the quantity of customer demand determines market pricing behavior. The cost of the ornamental plants is paid in cash at the time of purchase, and there has been cooperation between traders with communication to ensure the number of ornamental plants purchased and an agreement on the payment system that will be given after the plants are sold, resulting in good cooperation. Intertwined does not rely on dealers providing financing to farmers. Furthermore, channel patterns 1,2 and 3 have no Marketing Efficiency, whereas channel 4 patterns have 46 percent and channel 5 patterns have a ratio of 48 percent. As a result, channels 4 and 5 are deemed inefficient.